Resposta: x = 3
3x - 4 = 8
Resposta: x = 4
5x + 7 = 32
Resposta: x = 5
4x - 3 = 13
Resposta: x = 4
2x + 3 = 7x - 4
Resposta: x = 1,4
6x + 9 = 3x - 4
Resposta: x = -1,55
8x - 10 = 6x + 14
Resposta: x = 6
2x + 1 = 5x - 2
Resposta: x = 1,5
3x - 5 = 10 - 2x
Resposta: x = 1,5
4x + 7 = 3x - 8
Resposta: x = -15
5x + 2 = 3x + 10
Resposta: x = 4
2x - 3 = 5 - x
Resposta: x = 2
6x - 8 = 4x + 12
Resposta: x = 5
3x + 4 = 2x + 9
Resposta: x = 5
4x - 6 = 10 - 2x
Resposta: x = 2
7x + 2 = 4x - 5
Resposta: x = -1,4
9x - 5 = 2x + 11
Resposta: x = 2
5x + 3 = 8x - 9
Resposta: x = 4
6x - 7 = 5x + 8
Resposta: x = 15
2x + 6 = 3x - 2
Resposta: x = -8